Effects of Head Position on Perception of Gravity in Vestibular Neuritis and Lateral Medullary Infarction - Kim, Sung-Hee; Kim, Ji-Soo (Frontiers in Neurology, 2018)
Objective. Internal representation of gravity can be quantified by measuring the subjective visual vertical (SVV). Modulation of verticality perception during head tilts may be perturbed in vestibular disorders causing SVV tilts in the upright head position. This study aimed to determine the influence of head tilts on the estimation of SVV in acute vestibular disorders. Methods. We measured the SVV in 37 patients with acute vestibular symptoms due to unilateral vestibular neuritis (n=28) and lateral medullary infarction (n=9). Measurements of the SVV were performed under head upright, head tilt 30˚ and 60˚ in each direction. Seventeen normal subjects served as the control. Results. In controls, head tilt of 30° produced a contraversive shift of the SVV (the E-effect), and head tilt of 60° generated an ipsiversive shift (the A-effect). Patients with vestibular neuritis showed only the A-effect irrespective of the direction and amplitude of head tilt. Patients with lateral medullary infarction could estimate earth verticality accurately during head tilts. Patients with vestibular neuritis during the recovery phase showed the patterns of SVV modulation similar to those observed in the controls either with head upright or tilted. Conclusion. Given the absence of the E-effect in acute vestibular neuritis, the peripheral otolithic inputs appear to be essential in the perception of earth vertical during small static head tilts.